Potensi Sumberdaya Batubara di Daerah Petak Malai, Kabupaten Katingan, Provinsi Kalimantan Tengah - Asmoro Widagdo; Adi Candra (Jenderal Soedirman University, 2013)
Administratively, research area ( 9.930 Ha) is located at Petak Malai District, Katingan Regency, Central Kalimantan Province. This research is aimed to know the coal outcrop position, the number of coal seam and to measure of coal resources. The research is done by geological mapping of coal and other lithology at the field. The next phase is correlate some of coal outcrop and make a geological map. The last phase is calculating measured resource and indicated resource of all coal seams.There are ten of coal outcrops in the research area. The ten coal outcrop can be correlate and it becomes three coal seams which have 0.13 m to >0.7 m thick. This coal outcrop is found at Claystone-Sandstone Unit of Dahor Formationwhich lies at central part of the research area. Measured resource of coal resources calculation of research area is 873,050.1 ton. Indicated resource of this research area is 4,524,346 ton.Geological structure formed in the study area is fold and joint. The fold axis is relatively north-south trend. Anticline and syncline fold are the main control of the coal spread.